Increasing the development of national ideological values from an early age through family education - Sulistijaningsih, Sri; Nurdin, Encep Syarief; Fauziah, Puji Yanti; Dewi, Adin Ariyanti; Bariboon, Gumpanat (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
This research aims to determine the role of the family in training the application of Pancasila values in early childhood. The researchers used a literature review method to determine the role played by families in training young children to apply Pancasila valuesin everyday life. This research used Google Scholar and Scopus databases to search for relevant articles and conduct a more in-depth analysis. The research stage began with identifying previously determined keywords, screening by reading the abstract and research results and finding relevant articles to study. In analysis, the researcher conducted an analysis based on the context of the study of the selected articles until new themes emerged, which became the focus of the research. The theme was the role of family education in training Pancasila values from an early age. The results of the research showed that efforts to practice Pancasila values could be made by practising belief in God the Almighty, worshipping, respecting each other, praying, taking advantage of God's blessings, respecting older people, loving the environment, working together, respecting opinions, and being fair.